Comprehensive Analysis of a Yeast Lipase Family in the Yarrowia Clade. - Muchalin Meunchan; Stéphanie Michely; Hugo Devillers; Jean-Marc Nicaud; Alain Marty; Cécile Neuvéglise (PLoS ONE, 2015)
Lipases are currently the subject of intensive studies due to their large range of industrial applications. The Lip2p lipase from the yeast Yarrowia lipolytica (YlLIP2) was recently shown to be a good candidate for different biotechnological applications. Using a combination of comparative genomics approaches based on sequence similarity, synteny conservation, and phylogeny, we constructed the evolutionary scenario of the lipase family for six species of the Yarrowia clade. RNA-seq based transcriptome analysis revealed the primary role of LIP2 homologues in the assimilation of different substrates. Once identified, these YlLIP2 homologues were expressed in Y. lipolytica. The lipase Lip2a from Candida phangngensis was shown to naturally present better activity and enantioselectivity than YlLip2. Enantioselectivity was further improved by site-directed mutagenesis targeted to the substrate binding site. The mono-substituted variant V232S displayed enantioselectivity greater than 200 and a 2.5 fold increase in velocity. A double-substituted variant 97A-V232F presented reversed enantioselectivity, with a total preference for the R-enantiomer.